Diversity of Bradyrhizobia in Subsahara Africa: A Rich Resource - Grönemeyer, Jann Lasse; Reinhold-Hurek, Barbara (Frontiers in Microbiology, 2018)
Making use of biological nitrogen fixation with pulses and green manure legumes can help to alleviate nitrogen deficiencies and increase soil fertility, problems faced particularly in smallholder agriculture in Subsahara Africa (SSA). The isolation of indigenous rhizobia provides a basis for the formulation of rhizobial inoculants. Moreover, their identification and characterization contribute to the general understanding of species distribution and ecology. Here we discuss global species discovery of Bradyrhizobium spp.. Although recently the number of validly published Bradyrhizobium species is rapidly increasing, their diversity in SSA is not well represented. We summarize the recent knowledge on species diversity in the B. yuanmingense lineage to which most SSA isolates belong, and their biogeographic distribution and adaptations. Most indigenous rhizobia appear to differ from species found on other continents. We stress that an as yet hidden diversity may be a rich resource for inoculant development in future. As some species are exceptionally temperature tolerant, they may be potential biofertilizer candidates for global warming scenarios.